2004
DOI: 10.1111/j.1751-1097.2004.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of Various Quinolone Antibiotics in Aqueous—organic Solvent Mixtures¶

Abstract: The spectroscopic properties of enoxacin (ENO), oxolinic acid (OXO) and nalidixic acid (NAL) were studied in various H2O‐CH3OH and H2O‐CH3CN mixed solvents because these solvents were thought to behave as a biological mimetic system. ENO has piperazinyl group, but OXO and NAL do not have this substituent. The fluorescence emission spectra of ENO were very sensitive to the composition of the solvents. In the Lippert‐Mataga analysis of the steady‐state fluorescence data, clear reverse solvatochromism was exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…On going from THF to trifluoroethanol, there was about 1.6 times decrease in OF. Park et al (12) also reported a decrease of OF when the solvent was changed from methanol to acetonitrile. These results suggest that in protic solvents the intermolecular hydrogen bonding leads to structure IIb (Scheme 2) with a lower emission.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…On going from THF to trifluoroethanol, there was about 1.6 times decrease in OF. Park et al (12) also reported a decrease of OF when the solvent was changed from methanol to acetonitrile. These results suggest that in protic solvents the intermolecular hydrogen bonding leads to structure IIb (Scheme 2) with a lower emission.…”
Section: Resultsmentioning
confidence: 93%
“…In TFE the spectrum was blueshifted by 10 nm with respect to THF, suggesting that specific solute‐solvent interactions in the singlet excited state occurs. The shift in the emission spectrum could be also interpreted in terms of a small difference between the dipole moments of the S 0 and S 1 states (12). On the other hand, the fluorescence quantum yields slightly decrease in protic solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation